Olga Rovnova (November 23, 1960 — March 06, 2022) - Morozova, Nadežda (Slavistica Vilnensis, 2022)
On March 6, 2022, Olga Rovnova, a linguist and dialectologist, died after a serious illness. She studied the Old Believers for many years, was a specialist in Russian aspectology, as well as the Old Believers of Estonia and Latin America. She initiated interdisciplinary studies of the language and culture of the Old Believers’ chapels of South America, immigrants from China. In 2006–2008 Rovnova organized reconnaissance dialectological expeditions to Old Believer settlements in Argentina, Uruguay, Bolivia, and Brazil; in 2009, she visited the Old Believers of Australia (Sydney, Brisbane). The results of the researcher’s many years of field work are her numerous articles published in various scientific journals in Russia and abroad (a total of more than 140 scientific papers), scientific reports at Russian and international conferences, popular science educational speeches and lectures.